2004
DOI: 10.1007/s00431-004-1534-6
|View full text |Cite
|
Sign up to set email alerts
|

Addition of orlistat to conventional treatment in adolescents with severe obesity

Abstract: Orlistat could be a useful adjunct in the treatment of severe obesity in adolescents; however, gastrointestinal side-effects limit its usefulness in almost one in three adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(54 citation statements)
references
References 12 publications
2
46
0
6
Order By: Relevance
“…51 These approaches, explored in therapy for both adult and pediatric NASH, include (1) diagnosis and treatment of related metabolic disturbances such as diabetes and hyperlipidaemia (2) targeting IR by weight loss (healthy lifestyle: diet and exercise) or pharmacotherapy and (3) control of the secondary processes promoting to oxidative stress, inflammation, apoptosis and hepatic fibrosis by using hepatoprotective agents such as antioxidants. 6,26,[130][131][132][133][134][135][136][137][138][139] However, it is important to exclude secondary causes for hepatic steatosis. Treatment in these cases differs and revolves around correcting the underlying cause.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…51 These approaches, explored in therapy for both adult and pediatric NASH, include (1) diagnosis and treatment of related metabolic disturbances such as diabetes and hyperlipidaemia (2) targeting IR by weight loss (healthy lifestyle: diet and exercise) or pharmacotherapy and (3) control of the secondary processes promoting to oxidative stress, inflammation, apoptosis and hepatic fibrosis by using hepatoprotective agents such as antioxidants. 6,26,[130][131][132][133][134][135][136][137][138][139] However, it is important to exclude secondary causes for hepatic steatosis. Treatment in these cases differs and revolves around correcting the underlying cause.…”
Section: Treatmentmentioning
confidence: 99%
“…130 Table 5 has shown the list of pharmacological agents attributed to the treatment of NAFLD-NASH. [131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146][147] Only metformin 135 and vitamin E 140 have been used until now in clinical trials, but there is some evidence because of efficacy in adult and safety in children for other groups such as antiobesity (orlistat), 129,131 angiotensin-converting enzyme inhibitor 132 and stations. 133,138 These evidences in parallel to other novel therapies [141][142][143][144][145][146][147] must be considered in designing future clinical trials for treatment of pediatric fatty liver.…”
Section: Treatmentmentioning
confidence: 99%
“…A detailed study of the tolerability of taking orlistat together with a comprehensive behavioural and dietetic programme in 20 adolescents over 3 months found that 85% completed 3 months on orlistat, but that 50-60% reported a combination of unpleasant gastrointestinal side-effects [17]. In an early small open-label randomized controlled trial, gastrointestinal side-effects were reported in all 22 adolescents receiving orlistat, of whom seven (32%) dropped out of the trial during the first month of the trial due to side-effects attributable to orlistat [20].…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…Although absolute concentrations of vitamins D and E and b-carotene decreased during orlistat treatment, only few individuals needed supplementation in the European Multicenter Orlistat Study. 17 Two studies in extremely obese adolescents 20,21 and one study in obese prepubertal children 22 demonstrated that orlistat significantly reduces body weight. Unfortunately, all these studies were short-term trials (3 months), and only few patients remained on orlistat treatment for 15 months.…”
Section: Digestive Inhibitorflipase Inhibitor (Orlistat)mentioning
confidence: 99%
“…Unfortunately, all these studies were short-term trials (3 months), and only few patients remained on orlistat treatment for 15 months. The number of patients investigated was low: twenty, 20 twenty two, 21 and eleven. 22 What is more disturbing is that none of these trials were randomised and placebo-controlled.…”
Section: Digestive Inhibitorflipase Inhibitor (Orlistat)mentioning
confidence: 99%